2019
DOI: 10.1002/esp.4612
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the temporal evolution of soil redistribution rates in an agricultural landscape using 239+240Pu and 10Be

Abstract: Two principal groups of processes shape mass fluxes from and into a soil: vertical profile development and lateral soil redistribution. Periods having predominantly progressive soil forming processes (soil profile development) alternate with periods having predominantly regressive processes (erosion). As a result, short‐term soil redistribution – years to decades – can differ substantially from long‐term soil redistribution; i.e. centuries to millennia. However, the quantification of these processes is difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 78 publications
3
48
1
Order By: Relevance
“…2.5 Implementation and inverse modelling 2.5.1 Soil redistribution based on 239+240 Pu measurements Spatially distributed topsoil and subsoil bulk density and tillage depth information for each individual sampling location was applied to the proportional conversion approach. The reference inventory of undisturbed sites follows the value determined by Calitri et al (2019), who found a 239+240 Pu inventory of 43 ± 3 Bq m 2 based on four sites that did not show a profile morphological or geochemical indication of soil redistribution at a location 8.5 km from the study area. To address the uncertainty inherent to the reference measurements, a reference range from 40 to 46 Bq m 2 was accounted for in the simulations.…”
Section: +240 Pu-based Soil Erosion Assessmentsupporting
confidence: 53%
See 2 more Smart Citations
“…2.5 Implementation and inverse modelling 2.5.1 Soil redistribution based on 239+240 Pu measurements Spatially distributed topsoil and subsoil bulk density and tillage depth information for each individual sampling location was applied to the proportional conversion approach. The reference inventory of undisturbed sites follows the value determined by Calitri et al (2019), who found a 239+240 Pu inventory of 43 ± 3 Bq m 2 based on four sites that did not show a profile morphological or geochemical indication of soil redistribution at a location 8.5 km from the study area. To address the uncertainty inherent to the reference measurements, a reference range from 40 to 46 Bq m 2 was accounted for in the simulations.…”
Section: +240 Pu-based Soil Erosion Assessmentsupporting
confidence: 53%
“…The fallout radionuclides 239+240 Pu were used to estimate effective soil redistribution since the 1960s. Plutonium isotope measurements were conducted following Calitri et al (2019) based on the procedure of Ketterer et al (2004). Before the mass spectrometry analysis, 10 g of milled fine earth was dry-ashed for at least 8 h at 600 • C to remove organic matter.…”
Section: +240 Pu Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…1k yr. before present (Van der Meij et al, 2017;Kappler et al, 2018). In turn, tillage erosion is typically assumed to be a process that is linked to recent developments of increasing mechanical forces that are applied to soils over the past century (Sommer et al, 2008;Calitri et al, 2019). Within this study, a maximum topographical change by hilltop erosion up to 17 cm (53 yr) -1 was determined.…”
Section: Using 239+240 Pu and Inverse Modelling To Understand The Recmentioning
confidence: 99%
“…To date, most studies using FRN as a tracer for soil erosion have focused on agricultural soils (Schimmack et al, 2002; Calitri et al, 2019) or pastures (Tims et al, 2010; Lal et al, 2013; Alewell et al, 2013; Meusburger et al, 2018). In order to assess whether soil erosion rates are still sustainable, they need to be compared to the rates of soil production (Meusburger and Alewell, 2014; Alewell et al, 2015).…”
Section: Introductionmentioning
confidence: 99%